Looking for life : the role of theo-ethical reasoning in Paul's religion - Lewis, John G. (John Goddard), 1952- (London : T & T Clark International, 2005)
Revision of thesis (Ph. D) - - University of Oxford, 2004.
Cover; Editorial Board; Title; Copyright; CONTENTS; Acknowledgments; Abbreviations; Chapter 1 THEOLOGY AND ETHICS IN PAUL; Chapter 2 IDENTIFYING THEO-ETHICAL REASONING (1 CORINTHIANS 1.1-4.21); Chapter 3 ENGAGING IN THEO-ETHICAL REASONING: ASSOCIATING EXPERIENCE WITH CONDUCT (1 CORINTHIANS 5.1-16.24); Chapter 4 ENGAGING IN THEO-ETHICAL REASONING: LOOKING FOR LIFE IN CHRIST AND NOT IN LAW (GALATIANS); Chapter 5 CONCLUSION; Bibliography; Index of References; Index of Authors
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Epistles of Paul -- Theology; Paul, the Apostle, Saint -- Criticism and interpretation; Christian ethics; Protestant churches